(untitled) (Journal of Educational Sciences, 2016)
Мақалада автор тарих сабағында оқушыларда жаңа технологияны пайдалана отырып, саяси мəдениетін қалыптастыру туралы айтады. Urgency of forming political culture in pupils has been grounded in the article. The importance, place and role of the new instruction technology has been commented. Classification of the technologies of new instruction has been given. Lesson examples have been given with this purpose.